Taxpayers Compliance: Economic Level, Regulations Comprehension, Rates, and Transformation of Administration System - Roni Winner; Ardan Gani Asalam (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the influence of economic level, tax regulations comprehension, tax rates, and modernization of tax administration on the compliance of non-employee individual taxpayers in Bandung Cicadas Primary Tax Office. The research utilized a quantitative approach. Non-probability sampling technique, specifically Slovin Sampling, was employed with a sample size of 100 taxpayers, and data were collected through surveys. The research data was analyzed using descriptive statistics and multiple linear regression analysis using SPSS 26 software. The findings suggest that collectively, various factors including economic level, comprehension of tax regulations, tax rates, and modernization of tax administration, influence taxpayer compliance. Partially, the research reveals that both economic level and comprehension of tax regulations have a positive and significant impact on taxpayer compliance. However, tax rates and the modernization of the tax administration system do not significantly affect taxpayer compliance. These findings provide insights into tax compliance in Bandung Cicadas Primary Tax Office for tax authorities and regulators